Pendekatan Antropologis dalam Studi Islam - Huda, M. Dimyati (Didaktika Religia, 2016)
Anthropological approach to understand religion means an attempt to understandreligion by looking at the form of religious practices that are growing in society.Anthropology is a discipline that conveys the world view that depends on thescientific perspective, philosophical view, or religious beliefs. With this world viewone can understand their own world. By studying anthropology, we can realizethe cultural diversity of humankind and its influence in education. Education canbe defined as a process of learning, the provision of knowledge, skills and attitudes.Education can be obtained through formal and informal institutions. Teachingculture through informal institutions is done through enculturation in the familyenvironment. Finally, learners are guided to be responsible with all the knowledgethey have learned, to live in the society with thier potentials, and control naturefor the purpose of pleasing the holy God Almighty.